PELATIHAN GOAL SETTING “GOAL GETTER” UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - baroroh, Ema Zati; amalia, Kiki; Asri Azzahra, Mia; Putri, Santi Ramadhani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Low learning motivation is a common challenge for students, especially those with busy schedules at school and in Islamic boarding schools (pesantren). This study aims to test the effectiveness of the